PENGARUH SIKAP KONSUMERISME SISWA TERHADAP PENGGUNAAN SHOPPE PAY-LATER DALAM PANDANGAN EKONOMI ISLAM (STUDI KASUS PADA SISWA SMAN DI KABUPATEN TANGERANG) - Anzaningtyas, Mita (Universitas Islam Syekh Yusuf, 2022)
Shopee paylater is a feature found in the shopee application that uses the pay later principle. With these features, a person becomes more wasteful and has a consumerism attitude that is not good as a result of these features. This study aims to determine the effect of student consumerism on the use of shopee paylater in the view of Islamic economics (a case study on high school students in Tangerang Regency). This makes researchers want to find out more to students about